GluN2A and GluN2B NMDA receptors use distinct allosteric routes - Meilin Tian (Nature Portfolio, 2021)
NMDA receptors are glutamate-gated ion channels essential for synapse maturation and plasticity. Here the authors show that GluN2A and GluN2B NMDA receptors — the two principal subtypes NMDARs in the adult CNS — operate through distinct long range allosteric mechanisms.